2022
DOI: 10.1021/jacs.2c09378
|View full text |Cite
|
Sign up to set email alerts
|

Intercepting Elusive Intermediates in Cu-Mediated CO Electrochemical Reduction with Alkyl Species

Abstract: Understanding of the reaction network of Cucatalyzed CO 2 /CO electroreduction reaction [CO (2) RR] remains incomplete despite intense research efforts. This is in part because the rate-determining step occurs early in the reaction network, leading to short lifetimes of subsequent surface-bound intermediates, the knowledge of which is key to selectivity control. In this work, we demonstrate that alkyl groups can effectively couple with surface intermediates in the Cu-catalyzed CORR and, for the first time, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 56 publications
5
33
0
Order By: Relevance
“…The blue mechanism in (b) represent the likely pathway for ethylene glycol, glycolaldehyde, and glyoxal based on the results in this work, as also proposed by Garza et.al . The pathway in green is based on the results shown by Li et al and the trends observed in this work and the work of Delmo et al…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…The blue mechanism in (b) represent the likely pathway for ethylene glycol, glycolaldehyde, and glyoxal based on the results in this work, as also proposed by Garza et.al . The pathway in green is based on the results shown by Li et al and the trends observed in this work and the work of Delmo et al…”
Section: Resultssupporting
confidence: 69%
“…This approach is a useful strategy to experimentally identify potential intermediates, although it does not rule out the possibility of alternative C 2 intermediates participating in the reaction pathway. The reaction pathway for 1-propanol will not be discussed here as it has been discussed in detail elsewhere. Additionally, a small amount of hydroxyacetone (FE < 0.05%) was detected, which was also observed by Kuhl et al However, unlike 1-propanol, the reaction mechanism for hydroxyacetone formation has not yet been investigated. Interestingly, based on the reduction of hydroxycarbonyls, as shown in Figure S7, as hydroxyacetone was detected, it is also expected to form 1,2-propanediol and acetone since its reduction leads to these molecules at −1.0 V. Nonetheless, it is possible that these products were formed, but their productivity was below the chromatograph’s detection limit.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations